Insight into the origin of photoreactivity of various well-defined Bi2WO6 crystals: exposed heterojunction-like surface and oxygen defects. Issue 23 (15th February 2016) - Ma, Yongchao; Liu, Qingzhi; Wang, Qi; Qu, Dan; Shi, Jinsheng
Abstract : Three kinds of Bi2 WO6 with well-defined morphology were prepared. The nanosheet with exposed (020) facets was obtained. The origin of photoreactivity of Bi2 WO6 photocatalysis was studied. Abstract : An integrated examination of various influence factors ( i.e., atomic, electronic and defect structure) is necessary to obtain an accurate structure–function relationship. In this work, we reported the synthesis of three kinds of well-defined Bi2 WO6 photocatalysts with the aim of studying their atomic, electronic and defect-dependent photocatalytic properties. With examination of multiple characterization methods, it was found that nanosheets with a high percentage of exposed (020) facets were obtained. In addition, compared with single-crystalline nanosheets and nanoparticle-built microspheres, the nanosheet-assembled microspheres possess more surface oxygen defects. The visible light photoactivities of the prepared Bi2 WO6 samples were carefully investigated by degradation of various pollutants ( i.e., cationic Rhodamine B (RhB), anionic methyl orange (MO) and neutral ciprofloxacin (CIP)). The results revealed that the nanosheet-assembled Bi2 WO6 microspheres show the best visible light photoactivities, which may be ascribed to the cooperative effect between the exposed facets and high surface oxygen defects. The results presented in this study clearly demonstrate the exposed facet and defect structure codependence of photoreactivity, which provides further insights into the orgin of activity in semiconductor photocatalysis.